Influence of infrastructure material composition and microtopography on marine biofilm growth and photobiology. Issue 7 (9th August 2021) - Vivier, Baptiste; Claquin, Pascal; Lelong, Christophe; Lesage, Quentin; Peccate, Mathias; Hamel, Bastien; Georges, Marine; Bourguiba, Amel; Sebaibi, Nassim; Boutouil, Mohamed; Goux, Didier; Dauvin, Jean-Claude; et al.
Abstract: The impact of concrete composition and roughness on the formation of microalgal biofilms and their photobiology were studied on marine infrastructures presenting four different compositions combined with two degrees of roughness (rough and smooth). The structures were first inoculated with a natural microphytobenthic biofilm and immersed in sterilised seawater with a controlled photoperiod for six days. Photosynthetic activity was assessed with an imaging PAM-(Pulse Amplitude Modulated) fluorometer and microtopography was monitored in parallel with a 3-D camera. The results indicated that roughness had an impact on the biofilm biomass, its physiological status and its photosynthetic efficiency and capacity. The assessment of surface roughness indicated that negative reliefs were preferably colonised by MPB (microphytobenthic) cells with better photosynthetic performances. Moreover, MPB biofilms showed better photoacclimation in these microhabitats than on the positive and smooth reliefs. This study confirms the importance of microhabitat for biofilm formation and their photobiology.